Capparis spinosa L. tablet: from traditional to modern dosage form - Somayeh Esmaeili; Behnaz Keramatian; Haniyeh Kashafroodi; Rasool Choopani; Homa Hajimehdipoor (Institue of Medicinal Plants, ACECR, 2022)
Background: Capparis spinosa is used in Persian medicine for treatment of various diseases. In order to easier use, better patient's acceptance and more stability, preparing a suitable dosage form is necessary. Objective: The aim of the study was preparing tablet form from caper fruits and quality assessment of the product. Methods: The fruit extraction was performed using ethanol 80% and maceration technique and the extract was dried by freeze dryer. Eight formulations were made using lactose, avicel PH-102, SiO2 and magnesium stearate. The best formulation was failed during stability tests; therefore, the extract was dried by spray drying method along with maltodextrin and SiO2 as excipients. Eight formulations were prepared using lactose, avicel PH-102, croscarmellose sodium, PVP K30 and magnesium stearate and the best one was selected. Physicochemical and microbial assessments were performed on the selected formulation and stability tests were done in 40°C and 75% humidity as well as 30°C. Results: Caper tablets with freeze dried extract were deformed and their color changed but tablets with spray dried extract were stable in 30°C. They were oblong, green-blue, biconvex, scored tablets with 20.3×9.9×6.7 mm dimensions. Weight, hardness, disintegration time, rutin assay and dissolution were 1115 mg ± 10%, 18.33 ± 1.52 kp, 15±3.5 min, 0.58 ± 0.02 mg/tab and 93.03 ± 3.61 % in 60 min, respectively. Conclusion: Caper tablets are good candidate for production in industrial scale after in vivo and clinical studies. Moreover stability assessment of the tablets should be performed in suitable packaging in long term study.